Does Religious Affiliation Affect Students’ Entrepreneurial Intention? = Ali verska pripadnost vpliva na podjetniško namero študentov? - Ljubotina, Predrag (Edinost in dialog, 2024)
In the present research, we have analysed the differences between important global religious orientations in entrepreneurial intention, which the student population shows when making a career decision. Using quantitative approach, we investigated the influence of personal and environmental factors on students' entrepreneurial intention at a global level. 154,535 students from 52 countries participated in the survey. We examined and detected the different influences of individual factors on students' entrepreneurial intention in four observed groups: Buddhism, Christianity, Islam and individuals who do not belong to any religion. Important differences were detected between the groups, which can help state and religious institutions create their programs and activities to fulfil their mission. Our findings show that members of Islam have the strongest entrepreneurial intention. The lowest level of entrepreneurial intention was detected among students who do not follow any religion. In all groups, men express a stronger entrepreneurial intention compared to women. Among the members of Islam, we detected significant differences compared to the other groups, namely in the influence of the university environment, locus of control and subjective norms. Similarly, we found that the perceived level of inequality in society significantly shapes the entrepreneurial intention among Muslims and individuals who do not follow any religion, while there is no such influence among Buddhists and Christians. In addition to the above, the research findings also opened up several new questions, which we want to be the motive for further in-depth research.